2007
DOI: 10.1038/emm.2007.8
|View full text |Cite
|
Sign up to set email alerts
|

Sodium tanshinone IIA sulfonate depresses angiotensin II-induced cardiomyocyte hypertrophy through MEK/ERK pathway

Abstract: Cardiomyocyte hypertrophy is a major cause of morbidity and mortality worldwide. The aim of this study is to determine the effects of sodium tanshinone IIA sulfonate (STS) on cardiomyocyte hypertrophy induced by angiotensin II (Ang II) in vivo and in vitro. In long-term treatment, adult Wistar rats were infused with Ang II for three weeks via osmotic mini-pumps and some of them were given intragastrically of STS. Left ventricle was isolated; the ratio of left ventricular weight to body weight and systolic bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 34 publications
1
47
0
Order By: Relevance
“…Tanshinone IIA is most abundant and structurally representative of the tanshinones of Salvia miltiorrhiza (Tang and Eisenbrand, 1992). Recently, STS was shown to be a promising drug that reduced cardiac remodeling through depressing cardiomyocyte hypertrophy (Yang et al, 2007). Moreover, STS was shown to possess antioxidant action (Zhou et al, 1999(Zhou et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Tanshinone IIA is most abundant and structurally representative of the tanshinones of Salvia miltiorrhiza (Tang and Eisenbrand, 1992). Recently, STS was shown to be a promising drug that reduced cardiac remodeling through depressing cardiomyocyte hypertrophy (Yang et al, 2007). Moreover, STS was shown to possess antioxidant action (Zhou et al, 1999(Zhou et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…According to the difference of adhesive time consumption between cardiomyocytes and fibrocytes, cardiomyocytes were enriched using a differential adhesion technique. Bromodeoxyuridine (0.1 mM; Sigma) was added to the medium to inhibit proliferation of non-cardiomyocytes, as previously reported [15], and the produced cultures with 90%-95% of cardiomyocytes were assessed by microscopic observation.…”
Section: Asc Immunophenotypes and Differentiationmentioning
confidence: 99%
“…It has been demonstrated that tanshinone IIA exerts a variety of biological activities in the cardiovascular system, serving as an antioxidant and anticoagulant, and possesses anti-atherosclerotic, anti-apoptotic and anti-hypertrophic properties (5)(6)(7)(8)(9). Accumulating evidence suggests that tanshinone IIA reduces the area of ischemic infarction and improves cardiac function (7,10).…”
Section: Introductionmentioning
confidence: 99%